In search of amorphization-resistant boron carbide. (October 2016) - Subhash, Ghatu; Awasthi, Amnaya P.; Kunka, Cody; Jannotti, Phillip; DeVries, Matthew
Abstract: Despite its superior mechanical properties, boron carbide suffers from amorphization, a pressure-induced phenomenon that disturbs crystalline order and likely reduces shear strength. Numerous experimental and computational studies have investigated the structure and origins of amorphization, yet strategies to mitigate this deleterious phenomenon elude. However, recent investigations have revealed three new research avenues for addressing this issue. First, we identify crystallographic cage spaces that may accommodate foreign atoms to potentially prevent structural collapse. Second, we propose polymorph-level tailoring through strict control of processing conditions. Finally, we demonstrate that reducing grain size to nanometer scale increases hardness and may counter amorphization. Graphical abstract: